Nanoemulsion Formulation for Enhanced Delivery of 5-Fluorauracil and Resveratrol with Advanced Techniques - Mr. Sivakumar Theegala; Dr. Rajasekaran. S M Pharm, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
This study focuses on the formulation and optimization of a nanoemulsion-based lipid nanosystem for the dual delivery of 5-fluorouracil (5-FU) and resveratrol (RSV) to enhance dermal drug permeation and therapeutic efficacy. A systematic approach was employed to evaluate excipient screening, lipid selection, emulsifier efficiency, and formulation techniques. Labrasol® (LBR) was identified as the optimal medium-chain oil (MCO) due to its high drug solubility and P-GP inhibitory activity, while Emulcire® 61 WL 2659 (EML) was chosen as the solid lipid for its excellent emulsification properties and stability. Among the various formulation methods tested (S, M, H, K), Method-K, involving double emulsification, demonstrated superior stability, smaller particle sizes, lower polydispersity index (PDI), and higher drug entrapment efficiency (%EE) compared to other methods. Drug-excipient interaction studies using DSC and Fourier-transform infrared spectroscopy (FTIR) confirmed the compatibility and stability of 5-FU and RSV within the optimized formulation. The developed nanoemulsion system exhibited promising potential for dermal drug delivery, with enhanced drug solubility, stability, and bioavailability. These findings provide a strong foundation for further clinical investigations into the use of lipid-based nanosystems for targeted skin cancer therapy. Binary mixture (BM) miscibility studies confirmed LBR and EML as the ideal lipid combination, further optimized using differential scanning calorimetry (DSC) analysis. Tween® 80 emerged as the most effective emulsifier due to its superior emulsification properties and enhancement of membrane fluidity, facilitating drug permeation.